PENILAIAN TINGKAT RISIKO BENCANA TSUNAMI UNTUK KAWASAN KOTA BANDA ACEH BERDASARKAN SKENARIO TSUNAMI DESEMBER 2004 - Fauziah Fauziah; Eldina Fatimah; Syamsidik Syamsidik (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2014)
Realignment of Banda Aceh devastated by the tsunami has put forward the concept of disaster mitigation. As the city is aware of the disaster, the availability of disaster risk map is an essential requirement in developing sustainable development and disaster mitigation based. This research aims to generate a map of tsunami risk assessment by loading element of threat, vulnerability, capacity using spatial data and information in the region of Banda Aceh. Risk analysis is conducted using a semi-quantitative weighting factors and the index values arebased on the analysis conducted by BNPB and TDMRC-Unsyiah. Mapping analysis is conducted by overlaying layer(overlay) and vector-based GIS grid. Based on the results of the analysis show that the risk areas with low-to-high tsunami consists of 73 villages high with an area of each is 6.05 km2 (10%). 20.66 km2 (35%) and 16.23 km2. The area is not an area of 17.02 km2 risk or 28% of the total area of the city of Banda Aceh.